Influence of ZnO Morphology on the Functionalization Efficiency of Nanostructured Arrays with Hemoglobin for CO2 Capture - Alberto Mendoza-Sánchez; Francisco J. Cano; Mariela Hernández-Rodríguez; Oscar Cigarroa-Mayorga (Crystals, 2022)
In this study, nanostructured ZnO arrays were synthesized by an accessible thermal oxidation (TO) methodology. The Zn films were chemically etched with nitric acid (HNO3) and then oxidized in a furnace at 500 °C for 5 h. Two different morphologies were achieved by modifying the HNO3 concentration in the etching process: (a) ZnO grass-like nanostructures and (b) rod-like nanostructures, with an etching process in HNO3 solution at 2 and 8 M concentration, respectively. The physical and chemical properties of the samples were analyzed by X-ray diffraction (XRD), scanning (SEM) and transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), and Raman spectroscopy. Both morphologies were functionalized with hemoglobin, and a difference was found in the efficiency of functionalization, which was monitored by UV–Vis spectroscopy. The sample with the highest efficiency was the ZnO grass-like nanostructures. Afterward, the capture of carbon dioxide was evaluated by monitoring a sodium carbonate solution interacting with the as-functionalized samples. The evaluation was analyzed by UV–Vis spectroscopy and the results showed a CO2 capture of 98.3% and 54% in 180 min for the ZnO grass-like and rod-like nanostructures, respectively.